Iontosomes: Electroresponsive Liposomes for Topical Iontophoretic Delivery of Chemotherapeutics to the Buccal Mucosa - Kiran Sonaje; Vasundhara Tyagi; Yong Chen; Yogeshvar N. Kalia (Pharmaceutics, 2021)
The targeted local delivery of anticancer therapeutics offers an alternative to systemic chemotherapy for oral cancers not amenable to surgical excision. However, epithelial barrier function can pose a challenge to their passive topical delivery. The charged, deformable liposomes—“iontosomes”—described here are able to overcome the buccal mucosal barrier via a combination of the electrical potential gradient imposed by iontophoresis and their shape-deforming characteristics. Two chemotherapeutic agents with very different physicochemical properties, cisplatin (CDDP) and docetaxel (DTX), were co-encapsulated in cationic iontosomes comprising 1,2-dioleoyl-3-trimethylammonium-propane (DOTAP) and Lipoid-S75. The entrapment of CDDP was improved by formulating it in anionic reverse micelles of dipalmitoyl-sn-glycero-3-phospho-rac-glycerol sodium (DPPG) prior to loading in the iontosomes. Cryo-TEM imaging clearly demonstrated the iontosomes’ electroresponsive shape-deformable properties. The in vitro transport study using porcine mucosa indicated that iontosomes did not enter the mucosa without an external driving force. However, anodal iontophoresis resulted in significant amounts of co-encapsulated CDDP and DTX being deposited in the buccal mucosa; e.g., after current application for 10 min, the deposition of CDDP and DTX was 13.54 ± 1.78 and 10.75 ± 1.75 μg/cm2 cf. 0.20 ± 0.07 and 0.19 ± 0.09 μg/cm2 for the passive controls—i.e., 67.7- and 56.6-fold increases—without any noticeable increase in their transmucosal permeation. Confocal microscopy confirmed that the iontosomes penetrated the mucosa through the intercellular spaces and that the penetration depth could be controlled by varying the duration of current application. Overall, the results suggest that the combination of topical iontophoresis with a suitable nanocarrier system can be used to deliver multiple “physicochemically incompatible” chemotherapeutics selectively to oral cancers while decreasing the extent of systemic absorption and the associated risk of side effects.